Endoscopic and Pathological Characteristics of Cronkhite– Canada Syndrome: A Retrospective Analysis of 76 Cases - Wang, Wei; Shao, Yan; Zhao, Da-hua; Xue, Feng; Ma, Xing-bin; Li, Qiong; Liu, Cheng-xia (Turkish Journal of Gastroenterology, 2022)
Background: Cronkhite–Canada syndrome (CCS) is a disease of unknown etiology characterized by the presence of multiple gastrointestinal polyps, chronic diarrhea, loss of appetite, alopecia, onychodystrophy, and cutaneous hyperpigmentation. CCS is a rare diseasewith an incidence rate of 1 per million. Clinicians are not aware of this disease, and the discovery of gastrointestinal polyps is often astarting point for the diagnosis of this disease. By analyzing the endoscopic and pathological characteristics of CCS, this study aims todeepen our understanding of gastrointestinal polyposis and facilitate early diagnosis of CCS.Methods: We screened databases, including the Chinese Biomedical Literature Database (CBM Web), the China Academic Journals Fulltext Database (CJFD), and PubMed for CCS cases reported from January 2010 to January 2020, and conducted a retrospective analysisof endoscopic and pathological characteristics of these cases.Results: The endoscopic data of the 76 retrieved cases revealed that CCS is gastrointestinal polyposis with the intensive and confluent distribution. The greater the number of polyps and the higher their distribution, the brighter their color. A pathological assessmentrevealed that both gastric polyps and intestinal polyps are mainly juvenile hamartomatous polyps and have a high malignant transformation rate. Interstitial edema, eosinophil infiltration, and cystic dilation of glands are common features of CCS polyps, distinguishingthem from other gastrointestinal polyposis syndromes.Conclusion: CCS is a polyp disease different from other gastrointestinal polyposis. Analysis of its endoscopic and pathological characteristics can contribute to the understanding and early diagnosis of the disease.